2020
DOI: 10.1111/1759-7714.13556
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram prognostic model for patients with neuroendocrine tumors of the thymus

Abstract: Background The purpose of this study was to analyze the clinical characteristics and prognostic survival of patients with neuroendocrine tumors of the thymus (NETTs), and to develop and validate a nomogram model for predicting the prognosis of patients. Methods We conducted a retrospective analysis of patients with neuroendocrine tumors of the thymus in the Surveillance, Epidemiology, and End Results (SEER) database in the United States between 1988 and 2016. Cox scale risk regression analysis, the Kaplan‐Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In clinical practice, there is a need to predict the risk of VTE with greater accuracy, thus urgently warranting the development of specific risk assessment models for gynecological tumors. Nomogram is a practical and visualization tool useful for identifying high-risk patients and quantifying individual risk [34]. Considering this feature, we developed a nomogram model that can predict the occurrence of VTE in patients with gynecological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, there is a need to predict the risk of VTE with greater accuracy, thus urgently warranting the development of specific risk assessment models for gynecological tumors. Nomogram is a practical and visualization tool useful for identifying high-risk patients and quantifying individual risk [34]. Considering this feature, we developed a nomogram model that can predict the occurrence of VTE in patients with gynecological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only over 500 cases have been reported domestically and internationally [9][10][11][12][13] . In the 2015 WHO classi cation of thymic tumors,thymic neuroendocrine tumors are divided into 5 subtypes: typical carcinoid, atypical carcinoid, large cell neuroendocrine carcinoma, thymic carcinoma combined with large cell neuroendocrine carcinoma, small cell carcinoma, and thymic carcinoma combined with small cell carcinoma.This study summarizes over 500 cases of thymic neuroendocrine tumors reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The most important prognostic factors include tumor size, tumor stage, grade of tumor differentiation, surgical resectability, and surgical margin ( 2 , 8 , 14 , 24 , 31 , 37 ). Tang et al developed a nomogram prognostic model that could predict OS of thymic neuroendocrine tumors, consisting of T stage, tumor grade, surgical resectability, and whether the patient received chemotherapy, and found that their model had better authentication capability than Masaoka-Koga and TNM staging system ( 38 ).…”
Section: Discussionmentioning
confidence: 99%